The Effect of Leading Arabs, Who Wewe Executed With The Order of Cemal Pasha by The High Martial Cort, on The Arabic Seperatist Movements - Toprak, Seydi Vakkas (Fırat University, 2017)
In the 19th century while non-muslim ethnic and religious elements were uprising to found their own national states, Muslim Arabs and Turks took a stand to live together and they envisioned their political future with Ottoman State. At the beginning of the 19th century while there were Arab intellectuals and leaders acting in unison with The Committee of Union and Progress which was advocating centralist governance there also were the ones who advocated decentralization. However, after they took power and had an inclination for Turkish nationalism, among Arab thinkers and intellectuals some appeared bringing decentralization and independence models to the agenda. After The First World War started, even though the number of Arabs who acted in unison with The Ottoman State were a lot, in Arabia, Egypt and Syria nationalist and separatist Arab writers and thinkers founded committees and started to organize their supporters. In Syria, during the war the 4th Army commander Cemal Pasha firstly though tried to have an agreement with the Arabic separatist movements but he could not succeed and decided to clear the nationalist Arabs away. 34 people who were arrested by the order of Cemal Pasha and transferred to Aliye Divan-ı Harbi Örfi, under the force of Cemal Pasha, were sentenced to death and executed. While there are historians advocating that Cemal Pasha prevented an Arab rebellion and ensured public order by punishing national Arabic leaders, some others claim that these executions set the stage for Sheriff Hussein Pasha`s uprising. In this study the effect of executions carried out by Aliye Divan-ı Harbi Örfi on the Arab uprising against The Ottoman State in the course of The First World War is argued.

Osmanlı uyruğundaki gayrimüslim etnik ve dini unsurların milli devletlerini kurmak amacıyla isyan ettiği XIX. yüzyılda, Müslüman Araplar Türklerle birlikte yaşamaktan yana tavır takınmışlar, siyasi geleceklerini Osmanlı Devleti ile birlikte tasavvur etmişlerdir. XX. yüzyıl başlarında, merkeziyetçi bir yönetimi savunan İttihat ve Terakki Cemiyeti ile birlikte hareket eden Arap aydın ve liderler olduğu gibi adem-i merkeziyeti savunanlar da olmuştur. Ancak İktidara geldikten sonra Jön Türklerin Türk milliyetçiliğine meyletmesi üzerine Arap yazar ve düşünürler arasında yerinden yönetim ve bağımsızlık modellerini gündeme getirenler ortaya çıkmıştır. Birinci Dünya Savaşı başladıktan sonra Osmanlı Devleti ile birlikte hareket eden Arapların sayısı çok olmakla birlikte Arabistan, Mısır ve Suriye’de milliyetçi ve ayrılıkçı Arap yazar ve düşünürler cemiyetler kurarak taraftarlarını örgütlemeye başlamışlardır. Savaş sırasında IV. Ordu Komutanı Cemal Paşa, Suriye’de, ilk olarak Arap ayrılıkçı hareketleriyle uzlaşmaya çalışmışsa da başarılı olamamış ve milliyetçi liderleri ortadan kaldırmaya karar vermiştir. Cemal Paşa’nın emriyle yakalanarak Aliye Divan-ı Harbi Örfisine sevk edilenlerden otuz dört (34) kişi, Cemal Paşa’nın baskısıyla ölüm cezasına çarptırılmış ve idam edilmiştir. Cemal Paşa’nın milliyetçi Arap liderleri cezalandırarak asayişi sağladığı ve Arpların isyan etmesini engellediğini savunan bilim insanları olduğu gibi, bu idamların Şerif Hüseyin isyanına zemin hazırladığını iddia edenler de vardır. Bu çalışmada, Aliye Divan-ı Harbi Örfisince icra edilen idamların, Osmanlı Devleti’ne karşı Birinci Dünya savaşı sırasında çıkan Arap isyanına etkisi tartışılmıştır.
CEMAL PAŞA’NIN EMRİYLE ALİYE SIKIYÖNETİM MAHKEMESİNCE İDAM EDİLEN ARAP İLERİ GELENLERİNİN ARAP AYRILIKÇI HAREKETLERİNE ETKİSİ